A comparative assessment of technical and operational efficiency between small and large scale cavendish banana postharvest processing facilities a study in Panabo City - Malnegro, Mary Shenna A.; Olalo, Kristin Faye M. (2019)
This paper aims to measure and compare the efficiency values of small and large scale Banana Postharvest Processing Facilities and determine which facility is best observed when it comes to Technical Efficiency (TE), Operational Efficiency (OE) and Space Efficiency (SE). The study utilizes photo documentation and frequency analysis to get the ideal furniture and fixture dimension (height and reach) and also Data Envelopment Analysis (DEA) to get the efficiency values of the facilities. Using photo documentation, the study found out that both small and large scale facilities have problems regarding to ergonomics particularly at the following tasks; (1) arrival from field, (2) debagging, (3) maturity check and QI,(4) sampling, (5) SI Wash,(6) ribbon cut,(7) de-handing,(8) de-crowning, sorting and grading,(9) clustering,(10) weighing,(11) postharvest treatment,(12) labeling and foam insertion,(13) packing,(14) vacuum, and (15) palletizing, for the packing-house facility while (1) sorting,(2) peeling, (3) trimming, and (4) chipping activities for the banana rejects processing facility. Using frequency analysis, the study identified the ideal height of fixtures and furniture inside the facility based on a survey data of 71 anthropometric profiles of the workers from 7 postharvest processing facilities. With the help of input and output variables from the facilities, TE, OE and SE scores were computed under CRS (Constant returns to scale) assumptions through DEA (Data Envelopment Analysis). It was found out that large scale facilities are more efficient compared to small scale facilities when it comes to technical and operational aspects due to the following reasons; (1) access to adequate knowledge on postharvest processing, (2) efficient fruit care, (3) managerial aspects, (4) proximity of the facility to the farm, (5) efficiency monitoring, (6) energy conservation and waste management. However, large scale facilities were not efficient in terms of space due to too much space allotted for store-yard, packaging material storage and dryer that is not appropriate to its production capacity. In addition, it was found out that configuration of the workplace (L,N,U-type) does not have significant impact to the efficiency of the workplace as layout is dependent on the location of the entry point of produce from farm to facility, process flow to create finished product, and area of the facility.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2019